La comunicación didáctica en el trastorno del lenguaje expresivo, para desarrollar habilidades cognitivas en los alumnos de segundo año de Educación Básica de la Escuela Ángel Polibio Chaves de la ciudad de Guaranda, provincia de Bolívar, estudio realizado durante los meses de diciembre 2022 a marzo del 2023 - Quille Punina, Thalia Abigail (2023)
The present research project investigated how didactic communication affects expressive language disorders and cognitive development in 6 to 7-year-old children. Didactic communication is a tool that allows teachers to engage in conversations with students that foster motivation, active listening, and voluntary participation in the teaching-learning process. In addition, it benefits the development of language in children in areas such as speaking correctly, having an extensive vocabulary, understanding what is heard or read, following instructions, writing appropriately, and knowing how to relate to others. On the other hand, expressive language disorders affect children's ability to communicate effectively, which leads to the deterioration of cognitive abilities. Thus, the objective of the research was to develop cognitive skills through didactic communication. This was achieved through the development of a didactic guide that allows teachers to implement effective communication strategies in learning. The methodology of this project has a socio-critical paradigm since it was researched in the educational reality of teachers and students. Its approach is qualitative, and its objective was to understand the complexity and subjectivity of social reality to generate useful and relevant knowledge. The type of study used during the research was applied and developmental, aimed at solving practical problems in society, while the method used was descriptive, which allowed for the analysis and description of phenomena or events as they are